Structural and Functional Alterations of Substantia Nigra and Associations With Anxiety and Depressive Symptoms Following Traumatic Brain Injury - Gao, Liang; Xue, Qiang; Gong, Shun; Li, Gaoyi; Tong, Wusong; Fan, Mingxia; Chen, Xianzhen; Yin, Jia; Song, Yu; Chen, Songyu; Huang, Jingrong; Wang, Chengbin; et al. (Frontiers in Neurology, 2022)
Backgrounds: Although there are a certain number of studies dedicated to the disturbances of dopaminergic system induced by traumatic brain injury (TBI), the associations of abnormal dopaminergic system with post-traumatic anxiety and depressive disorders and their underlying mechanisms have not been clarified yet. Methods: Thirty-three TBI individuals and twenty-one healthy controls were recruited in the study. Anxiety and depressive symptoms were examined by the Hospital Anxiety and Depression Scale. All MRI data were collected using a Siemens Prisma 3.0 Tesla MRI system. The volume of substantia nigra (SN) and the global functional connectivity of SN and ventral tegmental area were analyzed. Results: In the present study, TBI patients reported more anxiety and depressive symptoms. More importantly, some structural and functional alterations, such as smaller SN and reduced functional connectivity in the left SN, were seen in TBI individuals. Among these findings, functional connectivity between left SN and left angular gyrus was positively associated with post-traumatic anxiety symptoms and negatively associated with depressive symptoms. Conclusions: TBI causes leftward lateralization of structural and functional alterations in the substantia nigra. Impaired mesocortical functional connectivity might be implicated in the post-traumatic anxiety and depression.